2011
DOI: 10.1177/230949901101900128
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis Variolosa: A Case Report

Abstract: Osteomyelitis variolosa is an infection of bone and joints by smallpox virus variola major, most commonly in the elbows, wrists, ankles, hands, and feet. We report one such case in a 70-year-old woman who presented with deformities of the right knee, both elbows and ankles, and the left hand, and a history of childhood fever with rashes. Her lateral femoral condyle of the right knee was hypoplastic with patella baja. Her right elbow was ankylosed and her left elbow was dislocated with multidirectional instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…A Arora, A Agarwal, S Kumar (2008) 3 2 Pathological fracture, Secondary arthritis Humerus, radius, ulna, ankle, feet Douraiswami Balaji (2011) 4 1 Secondary arthritis Distal femur, patella, humerus, metacarpals, ankle. Nema et al (2011) 5 1 Secondary arthritis Distal Humerus, Metacarpals, metatarsals, phalynx, calcaneum Andrews et al 2011 8 1 Asymptomatic Humerus, radius, Ulna, metacarpals Mugalur et al (2015) 6 1 Secondary arthritis Humerus, radius, Ulna, Metacarpals, ankle Singh PK 2012 9 1 Pathological fracture Humerus, radius, Ulna, Metacarpals Thomas J 2017 7 1 Secondary arthritis Humerus, radius, Ulna, Metacarpals, ankle Present study 1 Asymptomatic incidental finding Humerus, radius, Ulna, malformation of the bones (frequently with an intact joint space), flail joints and ultimately osteoarthritis.…”
Section: Studies and Number Of Cases Patients Presentation Bones Affementioning
confidence: 99%
See 1 more Smart Citation
“…A Arora, A Agarwal, S Kumar (2008) 3 2 Pathological fracture, Secondary arthritis Humerus, radius, ulna, ankle, feet Douraiswami Balaji (2011) 4 1 Secondary arthritis Distal femur, patella, humerus, metacarpals, ankle. Nema et al (2011) 5 1 Secondary arthritis Distal Humerus, Metacarpals, metatarsals, phalynx, calcaneum Andrews et al 2011 8 1 Asymptomatic Humerus, radius, Ulna, metacarpals Mugalur et al (2015) 6 1 Secondary arthritis Humerus, radius, Ulna, Metacarpals, ankle Singh PK 2012 9 1 Pathological fracture Humerus, radius, Ulna, Metacarpals Thomas J 2017 7 1 Secondary arthritis Humerus, radius, Ulna, Metacarpals, ankle Present study 1 Asymptomatic incidental finding Humerus, radius, Ulna, malformation of the bones (frequently with an intact joint space), flail joints and ultimately osteoarthritis.…”
Section: Studies and Number Of Cases Patients Presentation Bones Affementioning
confidence: 99%
“…5,6,8,9 There is deformity, instability and disorganization around the wrist and ankle joint caused by the disease process. 3,4,6,7 Ankle involvement is further complicated by collapse of the talus. 4 Arora et al 3 and Singh 9 reported a distal humerus fracture around the elbow affected with osteomyelitis variolosa, which was managed operatively.…”
Section: Studies and Number Of Cases Patients Presentation Bones Affementioning
confidence: 99%
“…Balaji [ 7 ] reported one such case in a 70-years-old woman with hypoplastic lateral femoral condyle of the right knee, patella baja, ankylosed right elbow, dislocated left elbow with multidirectional instability, short third and fourth metacarpals of the left hand, bilateral valgus deformity of ankle with destruction of talus. Arora et al .…”
Section: Discussionmentioning
confidence: 99%
“…1315 Bone infections caused by Brucella suis , 16 Haemophilus influenzae , 17 Mycobacterium tuberculosis , 18 Mycobacterium ulcerans , 19 and pox viruses, 20,21 as well as those whereby bone lesions are secondary to Bacille Calmette-Guérin 22 or smallpox 23 vaccination, also have been reported in the literature. Although many gram-negative and gram-positive bacteria were reported to have caused osteomyelitis; the great majority of bone infections, however, is staphylococcal in origin and mostly caused by a single bacterium: Staphylococcus aureus .…”
Section: Pathologies and The Downsides Of The Traditional Clinicamentioning
confidence: 96%